Dream architecture : today's designs for tomorrow - Xing, Rihan (Edition Axel Menges, 2010)
Showcases the innovations that are contributing to architectural forms, this title includes parametric modelling that is enabled by computer-aided technology, environmentally friendly building skins, and HOPSCAs - a hybrid building type - that can house hotels, offices, parking, shopping, a convention centre, and apartments under one roof